First approach to extend cultivation technology of medicinally important mushroom, Ganoderma lucidum - Singh, Sona; Harsh, N SK (Mushroom Research, 2016)
Ganoderma lucidum is an important medicinal mushroom being used in clinical, pharmaceutical and nutritional industry as well as for the treatment of various diseases such as migraine, hypertension, arthritis, bronchitis, asthma, anorexia, gastritis, diabetes, constipation, hepatitis and cardiovascular problems. Medicinal importance and increasing demand of this mushroom emphasizes to develop easy cultivation technique of this mushroom. The cultivation technique was extended to small groups and marginal farmers of rural areas specially women and unemployed youth to improve their livelihood. The cultivation technique of divine medicinal mushroom G. lucidum was adopted by various mushroom growers and farmers of Dehradun and nearby areas.